A study on landscape identity of Seri Menanti old palace garden and its impacts towards Malay traditional heritage - Mokhtar, Nur Afiqah; Harun, Nor Zalina (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Seri Menanti is known as the Royal Town of Negeri Sembilan which is famous for its Minangkabau and Adat Perpatih cultures. This paper is about the study on the landscape identity of Seri Menanti Old Palace Garden and its impact towards Malay cultural heritage. The issue to be dealt with throughout this research is regarding to the existing landscape at Old Palace Garden that is not compatible with the cultural aspects and architectural forms of Seri Menanti Old Palace Garden. The aim is to recommend Traditional Malay Garden design for Seri Menanti Old Palace Garden’s landscape to increase cultural heritage value to that place. However, the objectives of the study are: first to identify the characteristic of existing landscape at Seri Menanti Old Palace Garden; secondly to study the good characteristic of Malay Traditional Garden for Royal Palace garden; and lastly, this study will examine the existing landscape in Seri Menanti Old Palace Garden and for it to be integrated with Traditional Malay Garden. This research uses the qualitative approach by employing site observation and document review as the main methods for data collection. The site observation includes mapping, inventory and taking photographs at site study area, Seri Menanti Old Palace Garden’s landscape. The reviews on Seri Menanti Old Palace include the good characteristics of the garden according the spatial layout of Malay Traditional Garden’s characteristics. The finding shows the landscape characters at Seri Menanti Old Palace garden are not really equivalent to the Malay Traditional Garden’s characteristics. As a conclusion, the study is very important to bring back the identity of Malay culture into the Palace Garden’s landscape design.